DESAIN KURIKULUM DAN MOTIVASI BELAJAR MAHASISWA - Kunradus Kampo (SIMAK, 2019)
This study aims to identify the concept of learning which will motivate the learning of accounting students based on the curriculum of the accounting study program in Makassar. The study sample was 87 students from several private universities in Makassar. The research method used was descriptive research that identified 5 learning motivation of accounting students, learning outcomes, lecturer learning methods, and lecturer ratings. The results showed that on average students had high learning motivation even though there were also some students who had low motivation. Students may have entrinsic motivation but they try to learn because they are motivated to get high scores. Accounting students understand the competencies to be obtained and are supported by varied learning methods from lecturers. These results may be explained by the results of a test of the relationship or association between learning motivation and GPA which indicates a relationship between the two. While learning motivation and duration of study, learning motivation and GPA, as well as GPA and duration of study there is no relationship or not associated with one another.